Implementasi Model Pembelajaran STEAM Dalam Meningkatkan Kreativitas Peserta Didik Di RA Al-Manshuriyah Kota Sukabumi - Neneng Nur; Mulyawan Safwandy Nugraha (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This study aims to explore and analyze the implementation of the STEAM Learning Model (Science, Technology, Engineering, Arts, and Mathematics) in increasing the creativity of students at RA Al-Manshuriyah. The STEAM learning model is an interdisciplinary approach that combines elements of science, technology, engineering, art, and mathematics in learning. This research was conducted with a qualitative approach and used the case study method as the research design. The results showed that the implementation of the STEAM Learning Model at RA Al-Manshuriyah succeeded in increasing the creativity of students. In this context, creativity is measured through indicators such as the fluency of ideas, the ability to think creatively, the flexibility of thinking, and respect for works of art and innovation. The STEAM model provides students with opportunities to develop creative thinking skills through interdisciplinary learning experiences and complex problem solving. In addition, this learning model also stimulates collaboration between students in team projects that allow them to share ideas and collaborate in creating innovative solutions. The implementation of STEAM also increases student adaptation to change and fosters appreciation for art and innovation. The STEAM Learning Model has proven its success in increasing the creativity of students at RA Al-Manshuriyah. These results illustrate the importance of an interdisciplinary educational approach to fostering student creativity in diverse educational settings. The implication of this research is the importance of continuing the development of the STEAM approach in the context of formal education to further optimize students' creative potential.